Probiotic therapy as adjuvant for allergic rhinitis: an overview of systematic reviews and meta-analyses - Wang, Zhuang; Song, Yongfu; Liang, Xue; Wang, Na; Li, Dongze; Xie, Xiaofei; Tian, Bing; Wang, Yongji (Frontiers in Medicine, 2026)
ObjectiveThis study aims to provide an overview of systematic reviews and meta-analyses on probiotic adjuvant therapy for allergic rhinitis, with the goal of offering evidence-based support for clinical practice and decision-making.MethodsA comprehensive search was performed in PubMed, Embase, Cochrane Library, Web of Science, CNKI, VIP, WANFANG, and CBM databases from their inception to 5 July 2025, to identify systematic reviews and meta-analyses on probiotic adjuvant therapy for allergic rhinitis. Constructing a literature overlap matrix and calculating the adjusted overlap area for assessing duplication rates in source literature. ROBIS, AMSTAR-2, PRISMA 2020, and GRADE were used to assess bias risk, methodological/reporting quality, and evidence certainty. Quantitative and qualitative analyses of primary outcomes provided comprehensive insights.ResultsFifteen systematic reviews and meta-analyses were included; the adjusted overlap area, calculated from the literature overlap matrix, was 16.939%, all demonstrating low bias risk. Methodological quality assessment identified 9 high-, 5 low-, and 1 critically low-quality study. The evaluation of reporting quality showed 7 high-, 7 moderate-, and 1 low-quality study. Evidence certainty grading yielded 11 high-, 37 moderate-, 35 low-, and 17 critically low-quality outcomes. Quantitative analysis confirmed that probiotic adjunct therapy significantly reduced eosinophil counts in patients with allergic rhinitis. Qualitative synthesis indicated probiotics alleviated symptoms, improved quality of life, and exhibited favorable safety as adjuvant treatment.ConclusionProbiotics show significant adjuvant value in allergic rhinitis, effectively alleviating symptoms and improving quality of life. Their immunomodulatory effects restore Th1/Th2 balance, while demonstrating excellent safety and tolerability for clinical application.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier: CRD420251087317.